Is Interval Training more Effective and Efficient Workout for Fat Loss Compared to Continuous Training?A Meta-Analysis - Sana Mehmood, Amna Aamir Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Enhancing regular physical activity can lead to substantial health benefits. Interval-based high-intensity circuit training is an effective and efficient way of reducing body fat, yet the comparison between this type of training and long-term moderate-intensity continuous training is equivocal. Objectives: the objective was to conduct a meta-analysis for comparing high-intensity interval training with moderate-intensity continuous training on improving body fat. Method: We searched PubMed, Google Scholar, Scopus, and CINAHL for the following inclusion criteria: (a) Studies that compare high-intensity interval training and moderate-intensity continuous training using body fat as an outcome measure in a healthy population; (b) the frequency of the training at least four weeks; (c) Articles must be in the English language. Result: A total of 325 participants were included in 10 Randomized Control Trials (RCT). Results revealed that interval training has a mild pooled effect in reducing the body fat of the participants with an effect size of (SMD) of 0.26 (95% of CI=0.00 to 74.84) calculated at the random effect model. I2 14.87% (95% CI=0.01 to 0.45) in comparison to moderate-intensity continuous training performed during 6-12 weeks. Conclusion: We concluded that the intensity of effort has a significant impact in reducing fat loss in minimal time compared to continuous long-term exercise with less intensity. Keywords: Body Fat, Continuous training, Interval-Training, Sprint interval, traditional exercises